Peran Kegiatan Musyawirin Dalam Melestarikan Tradisi Pesantren Pada Kalangan Remaja Di Desa Sumberdawesari Grati Pasuruan - Syaifi, Mat; Irfan Firdaus, Mukhammad (Universitas Nahdlatul Ulama Pasuruan, 2023)
Musyawirin activities are also called book deliberation activities, which are reading, studying and discussing in depth the contents of a book. This activity is one of the learning traditions in Islamic boarding schools. In practice, this deliberation fully adapts the existing implementation in Islamic boarding schools. Through this musyawirin activity they can practice and deepen their knowledge.The focus and research objectives in this study are, what is the role of deliberation activities, how are deliberative activities carried out, what are the supporting and inhibiting factors of deliberative activities in preserving the pesantren tradition among youth in Sumberdawesari grati pasuruan village. The type of research used by researchers is a type of qualitative research using an ethnographic approach. Sources of data used by researchers are primary and secondary. The results of the research are that the role of musyawirin activities is as a place to practice and deepen religious knowledge, as well as train self-confidence and emotion. The implementation of musyawirin includes; the structure in which there is; qori', mubayyin, mushohih, and mustami'in, then the implementation is on Wednesday night and the books studied are fathul qorib, fathul mu'in, and jamal. A flexible place and colleagues are the supporting factors for this activity, while lazy, inferior , and the lack of pious people is the inhibiting factor of these activities.